2016
DOI: 10.24200/sci.2016.3863
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Self-Assembly of the Surfactants into Biological Bilayer Membranes with Special Chemical Structure Using Dissipative Particle Dynamics Method

Abstract: Abstract. The aim of this study is to simulate the self-assembly of the surfactant molecules with special chemical structure and bending sti ness into bilayer membranes using a mesoscopic Dissipative Particle Dynamics (DPD) method. The surfactants are modeled with special chemical structure and bending sti ness. To con rm that the novel model is physical, we determine the interaction parameters based on matching the compressibility and solubility of the DPD system with real physics of the uid. To match the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[ 1 2 ] To have a better understanding of complex biological behaviors, mathematicians in collaboration with biologists have designed computer algorithms and mathematical relations that imitate biological phenomena. [ 3 ] Computational models are based on computer algorithms that mimic a natural process with every level of complexity such as models of thymocyte development, biochemical processes, and cell fate specification during Caenorhabditis elegans development. [ 4 5 6 ] The quantitative relationship between variables (gene activity level and molecular concentration) have been designed to indicate cell signaling pathways in a biologically and physically realistic manner and generate innovative and useful hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 2 ] To have a better understanding of complex biological behaviors, mathematicians in collaboration with biologists have designed computer algorithms and mathematical relations that imitate biological phenomena. [ 3 ] Computational models are based on computer algorithms that mimic a natural process with every level of complexity such as models of thymocyte development, biochemical processes, and cell fate specification during Caenorhabditis elegans development. [ 4 5 6 ] The quantitative relationship between variables (gene activity level and molecular concentration) have been designed to indicate cell signaling pathways in a biologically and physically realistic manner and generate innovative and useful hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results were in good agreement with those of the Stokes law. However, in many DPD simulations of colloidal and polymeric solutions, the colloidal particles and polymer beads were represented by individual DPD particles [2][3][4], which were proved to be e cient simulations. In this study, the equilibrium radial distribution function, g(r), as a function of distance is plotted and it will be observed that almost no particle can penetrate into this sphere.…”
Section: Introductionmentioning
confidence: 99%